Pengujian Impak Komposit Berpenguat Pelepah Salak untuk Aplikasi Pembuatan Papan Partikel - Subana, Aldi; Yuliyanto, Yuliyanto; Krishnaningsih, Shanty Dwi (Jurnal Inovasi Teknologi Terapan, 2024)
Wood is the main substance commonly used in the particle board manufacturing industry. However, the rate of forest destruction that continues to occur makes the availability of wood decrease. Alternative materials to replace wood are needed. The salak frond, the object of this study, is a non-wood material that can manufacture particle board. This study used the full factorial method to see the effect of impact testing by comparing the use of polyester matrix and salak frond powder in particle board specimens. The parameters in this study used variations in oven temperatures of 800, 1000, and 1200 degrees Celsius for 15 minutes and volume ratios between salak frond powder and polyester matrix 80:20, 70:30, and 60:40. From the test results, the highest mechanical properties of impact strength were obtained at a ratio of 70:30 with a temperature variation of 1000 and an average of 15.80 kJ/m2. The lowest value is found in a ratio of 60:40 with a temperature variation of 800 and an average of 6.65 kJ/m2. The test results of this study have exceeded the standard impact strength of particle board on the market, which is 3.201 kJ/m2